2015
DOI: 10.1155/2015/851721
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiproliferative Activities of the Essential Oils fromThymbra capitataandThymusSpecies Grown in Portugal

Abstract: The antioxidant and antiproliferative activities of the essential oils from Thymbra capitata and Thymus species grown in Portugal were evaluated. Thymbra and Thymus essential oils were grouped into two clusters: Cluster I in which carvacrol, thymol, p-cymene, α-terpineol, and γ-terpinene dominated and Cluster II in which thymol and carvacrol were absent and the main constituent was linalool. The ability for scavenging ABTS•+ and peroxyl free radicals as well as for preventing the growth of THP-1 leukemia cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
2
25
1
Order By: Relevance
“…caespititius and Th. mastichina EOs in the present work (assay performed in the presence of cyclodextrins), the values for which are almost tenfold higher than those reported [9], in which cyclodextrins were not introduced in the method. For the first time, the antioxidant activity of Th.…”
Section: Ricontrasting
confidence: 71%
See 1 more Smart Citation
“…caespititius and Th. mastichina EOs in the present work (assay performed in the presence of cyclodextrins), the values for which are almost tenfold higher than those reported [9], in which cyclodextrins were not introduced in the method. For the first time, the antioxidant activity of Th.…”
Section: Ricontrasting
confidence: 71%
“…Such a difference cannot only be attributed to carvacrol or thymol, since when separately assayed, they showed similar activities [11]. Miguel et al [9] found that different percentages of carvacrol in diverse Th. caespititius EOs or T. capitata EO could present similar antioxidant activity.…”
Section: Rimentioning
confidence: 99%
“…The standard curve was obtained by plotting Trolox concentrations against the average net AUC of the measurements for each concentration. Final ORAC values were calculated using the regression equation between Trolox concentration and the net AUC and were expressed as µmol TE/g EO [ 24 ]. Tests were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that the EO of T. capitata shows a potent antioxidant activity due to its high content of phenols (thymol or carvacrol) [37]. This statement is supported by Aazza et al [38], when compared with the antioxidant activity of several thyme species.…”
Section: Bioactivity Of T Capitata Eo 41 Antioxidant Activitymentioning
confidence: 78%
“…In addition, this toxicity can be used as antiproliferative activity in in vitro experiments, since the EO extracted from fruits of T. capitata inhibited the growth of cells isolated from cervical cancer (HeLa). Likewise, the EO extracted from flowers and fruits of this species inhibited the growth of histiocytosis cells (U937) [30] and tumor cells responsible for acute monocytic leukemia (THP-1) [37].…”
Section: Bioactivity Of T Capitata Eo 41 Antioxidant Activitymentioning
confidence: 97%